Good Amil Governance According to Zakat Core Principles: A Concept to Improve the Efficiency and Effectiveness of Zakat Management - Elvira, Rini; Yaswirman, Yaswirman; Effendi, Nursyirwan; Devianto, Dodi (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2023)
The importance of good amil governance in zakat management becomes increasingly urgent along with the complexity and size of the funds being managed. Practices involving transparency, accountability, responsibility, independence, fairness, and legal compliance are the keys to success in achieving efficiency and effectiveness in zakat management. Therefore, it is necessary to carry out further description and exploration regarding the concept of good amil governance based on zakat core principles. This research is a literature study that adopts a descriptive-exploratory qualitative approach. Secondary data sources were obtained from various literature, including journal articles, books, official reports from the BAZNAS Study Center, and government documents, as well as other relevant sources. The Systematic Literature Review (SLR) technique was utilized to optimize the data, which was then analyzed in depth using a descriptive-exploratory qualitative approach to present a comprehensive picture of the concept of good amil governance according to zakat core principles.